Boosting the photocatalytic activity of graphite carbon nitride by designing novel MoS2–transition metal heterojunction cocatalysts. Issue 42 (14th October 2019) - Li, Kui; Lin, Ye-Zhan; Zhang, Yu; Xu, Mei-Ling; Liu, Ling-Wang; Liu, Fu-Tian
Abstract : MoS2 –transition metal heterojunctions were adopted as cocatalysts on the earth-abundant g-C3 N4 and displayed a synergistic effect on improving the photocatalytic performance. Abstract : The design of highly effective noble metal-free cocatalysts plays an extremely important role in improving the photocatalytic solar energy conversion. Herein, we designed and synthesized a novel heterostructure form of MoS2 –transition metals (Fe, Co, and Ni) on g-C3 N4 nanosheets for obtaining a significant enhancement in the photocatalytic activity for hydrogen production and pollutant disposal. The electrochemical characterization and time-resolved photoluminescence results indicated that the unique tunable feature of the MoS2 –transition metals greatly reduced the hydrogen evolution reaction (HER) overpotential, increased the separation, transport and utilization efficiency of the photo-generated charge carriers, and displayed a synergistic effect in improving the electrocatalytic and photocatalytic HER performances. The ternary g-C3 N4 –MoS2 –metals exhibited extremely high photocatalytic HER rates of 1.7, 4.1, and 5.12 mmol h −1 g −1 for g-C3 N4 –MoS2 –Fe, g-C3 N4 –MoS2 –Co and g-C3 N4 –MoS2 –Ni, respectively, which were 2.7, 4.7 and 5.3 times larger than the sum of the photocatalytic HER activities of g-C3 N4 –MoS2 and the corresponding g-C3 N4 –metals. This work provides a facile and effective strategy for improving photocatalytic energy conversion using only earth-abundant non-noble cocatalyst heterostructures.